The Origins of State - Boix, Carles (World Bank, Washington, DC, 2017)
Here I explore the process leading to the formation of the state in two steps. In the first part of this research note, I examine the transition from stateless to state societies, that is, I characterize the conditions under which the state arises. In the second part, I analyze the consolidation of the state, that is, the conditions under which, once it has been established, the state remains in place and avoids falling back into what many have referred to as a “failed state”. In both parts I proceed in the same fashion. After presenting a “minimalist” or bare-bones theory, I briefly discuss the extent to which our empirical evidence seems to match the main insights of the theory.